The Excellence of "Surah Āl-e-‘Imran" and its Characteristics in Light of the Authentic Ahadith: An Analytical Study - Ghouri, Syed Abdul Majid (Journal of Islamic and Religious Studies, 2024)
"Sūrah Āl-e-‘Imrān" is one of the esteemed chapters in the Holy Quran. It calls for steadfastness in Islam after its completion and clarification, and it refutes the doubts of the People of the Book (Ahl-e-Kitāb), especially the Christians. Many prophetic Ahādīth mention its virtues, including that this Sūrah contains the Greatest Name of Allah, which is "Al-Hayy Al-Qayyūm" (The Ever-Living, The Sustainer), and that this Sūrah and "Sūrah Al-Baqarah" will argue on behalf of their reciters on the Day of Resurrection. Besides these, numerous authentic Prophetic traditions highlight the virtues and excellence of this Sūrah. This research deals with the study of what is mentioned in those Ahādīth about the virtues of the Sūrah, and then it outlines its characteristics in light of those Ahādīth. The researcher followed an inductive and analytical approach in this study. The inductive approach was utilized to trace and compile authentic Ahādīth pertaining to the excellence and characteristics of the Sūrah, while the analytical approach was used to analyze the texts of those Ahādīth and derive conclusions from them. The research concluded with a number of important findings, summarizing that anyone who wishes to act upon the teachings of this Sūrah and benefit from its unique characteristics must ponder and reflect upon its meanings, take heed and learn from the teachings, wisdom, commandments, and prohibitions of the Sūrah.